Implementasi Pendekatan Komunikatif dalam Pembelajaran Bahasa Arab di Pondok Pesantren Darul Lughah wal Karomah - Ahmad Fahim; Mu’alim Wijaya (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study examines the implementation of the communicative approach in Arabic language learning at the Language Development Institute (LPBA) of Pondok Pesantren Darul Lughah wal Karomah. It employs a descriptive qualitative design. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The trustworthiness of the findings was established through triangulation and member checking. The findings reveal that the communicative approach is applied through dialogue, group discussion, presentations, and daily language practice that integrates the four language skills. This approach contributes positively to students’ confidence and fluency in speaking. Nevertheless, grammatical accuracy and the consistency of the language environment remain key challenges. The study concludes that the communicative approach is effective in improving students’ speaking skills, although further improvement is needed in the evaluation system and in strengthening the language environment. These findings suggest the importance of structured communicative assessment and the consistent development of bi’ah lughawiyah within the institutional learning context.